Evaluation of bone excision effects on a human skull model - II: Finite element analysis - Franceskides, Constantinos; Gibson, Michael C.; Zioupos, Peter (Sage, 2019)
Patient-specific computational models are powerful tools which may assist in predicting the outcome of invasive surgery on the musculoskeletal system, and consequently help to improve therapeutic decision-making and post-operative care. Unfortunately, at present the use of personalized models that predict the effect of biopsies and full excisions is so specialized that tends to be restricted to prominent individuals, such as high-profile athletes. We have developed a finite element analysis model to determine the influence of the location of an ellipsoidal excision (14.2 mm × 11.8 mm) on the structural integrity of a human skull when exposed to impact loading, representing a free fall of an adult male from standing height. The finite element analysis model was compared to empirical data based on the drop-tower testing of three-dimensional-printed physical skull models where deformations were recorded by digital image correlation. In this bespoke example, we found that the excision site did not have a major effect on the calculated stress and strain magnitudes unless the excision was in the temporal region, where the reduction in stiffness around the excision caused failure within the neighboring area. The finite element analysis model allowed meaningful conclusions to be drawn for the implications of using such a technique based on what we know about such conditions indicating that the approach could be both clinically beneficial and also cost-effective for wider use
Keywords: Biopsy; skull fracture; strains; digital image correlation; impact loading; finite element analysis